The Development of Countering Monopolization in the Electric Energy Industry - Korolev, Vitaly G. (Journal of Environmental Accounting and Management, 2026)
The relevance of the topic is that countering monopolization in the economy and protecting competition is one of the important tasks of the state. The purpose of the paper is the analysis and determination of the directions of development of antimonopoly regulation in the electric energy industry in Russia. It was determined that the market is still monopolized, with rather strict regulation and significant barriers for new entrants. It is proposed to reduce these barriers for access to retail and wholesale markets for new participants, the development of digital energy for the development of competition.